Differential gene expression in Acidithiobacillus ferrooxidans LR planktonic and attached cells in the presence of chalcopyrite - Ossa Henao, Diana Marcela [UNESP]; Vicentini, Renato; Rodrigues, Viviane Drumond; Bevilaqua, Denise [UNESP]; Mariscal Ottoboni, Laura Maria (Wiley-Blackwell, 2014)
Acidithiobacillus ferrooxidans is commonly used in bioleaching operations to recover copper from sulfide ores. It is commonly accepted that A. ferrooxidans attaches to mineral surfaces by means of extracellular polymeric substances (EPS), however the role of type IV pili and tight adherence genes in this process is poorly understood. Genes related to the formation of type IV pili and tight adherence were identified in the genome of the bacterium, and in this work, we show that A. ferrooxidans actively expresses these genes, as demonstrated by quantitative real-time PCR analysis using cells incubated with chalcopyrite for 2 h. Significant differences in gene expression were observed between planktonic and adhered cells, with the level of expression being much greater in planktonic cells. These results might indicate that planktonic cells can actively adhere to the substrate. A bioinformatics analysis of interaction networks of the tight adherence and type IV pilus assembly genes revealed a strong relationship between conjugation systems (tra operon) and regulatory systems (PilR, PilS).
Keywords: Acidithiobacillus ferrooxidans; Type IV pili; Chalcopyrite; Gene expression; Real-time PCR